Mental Health Disorders are More Common in Colorectal Cancer Survivors and Associated With Decreased Overall Survival. (April 2019) - Lloyd, Shane; Baraghoshi, David; Tao, Randa; Garrido-Laguna, Ignacio; Gilcrease, Glynn W.; Whisenant, Jonathan; Weis, John R.; Scaife, Courtney; Pickron, Thomas B.; Huang, Lyen C.; Monroe, Marcus M.; Abdelaziz, Sarah; et al.
Abstract : Objectives: To determine the risk and risk factors for mental illness among colorectal cancer (CRC) survivors across short-term and long-term follow-up periods. Methods: We used the Utah Cancer Registry to identify CRC survivors diagnosed between 1997 and 2013. Mental health diagnoses were available in electronic medical records and statewide facilities data that were linked by the Utah Population Database. CRC survivors were matched to individuals from a general population cohort. The risk of developing a mental illness was compared between cohorts. The association between mental illness and mortality was also analyzed. Results: In total, 8961 CRC survivors and 35, 897 individuals in a general population cohort were identified. CRC survivors were at increased risk for any mental health diagnosis at 0 to 2 years (hazard ratio [HR], 3.70; 95% confidence interval [CI], 3.47-3.95), >2 to 5 years (HR, 1.23; 95% CI, 1.09-1.38), and >5 years (HR, 1.20; 95% CI, 1.07-1.36) after cancer diagnosis. CRC survivors were also at increased risk of depressive disorders specifically during the same time periods. At >5 years, CRC survivors still had an increased risk of developing many mental health diagnoses. Factors associated with increased risk of any mental health disorder among CRC survivors included colostomy and Charlson Comorbidity Index of 1+. There was an increased risk of death for CRC survivors diagnosed with any mental health disorder (HR, 2.18; 95% CI, 2.02-2.35) and depression (HR, 2.10; 95% CI, 1.92-2.28). Conclusions: CRC survivors are at increased risk for mental health disorders in the short-term and long-term. Survivors who develop mental health disorders also experience decreased survival.